Exploring the use of ICTs as a tool for job crafting - Handke, L.; De Boeck, Giverny; Parker, Sharon (2025)
In this paper, we integrate Action-Regulation Theory into job crafting research to explore workers' agency in using information and communication technologies (ICTs) to redesign their work. Specifically, using a sequential mixed-methods design, we investigate workers' proactive use of ICTs for job crafting. In Study 1, we explore workers' use of ICTs to change their job demands and job resources using interviews and identify seven underlying ICT use crafting tactics. In Study 2, we find support for the factorial structure of the seven ICT use crafting tactics and provide evidence of their relevance by testing the relationships between these seven tactics and established measures of job crafting, key antecedents of job crafting (proactive personality, personal initiative), and key outcomes of job crafting (skill utilization, person-environment-fit), using a two-wave survey. We discuss theoretical implications for the literature on job crafting and work-related ICT use, and formulate practical recommendations for organizations to support the use of ICTs as a tool for job crafting.